PENGEMBANGAN KURIKULUM PAI PENINGKATAN MUTU PEMBELAJARAN: Pengembangan Kurikulum PAI Pada Peningkatan Mutu Pembelajaran - rifai, rizal; Indasah (POJOK GURU: Jurnal Keguruan dan Ilmu Pendidikan, 2025)
Abstract The curriculum as an educational design has a fairly central position in all learning activities, determining the implementation process and educational outcomes. Considering the important role of the curriculum in education and in the future development of students' lives, curriculum development cannot be done haphazardly, it must be oriented towards clear goals so that it will produce good and perfect results. The curriculum as an educational design has a fairly central position in all learning activities, determining the implementation process and educational outcomes. Considering the important role of the curriculum in education and in the future development of students' lives, curriculum development cannot be done haphazardly, it must be oriented towards clear goals so that it will produce good and perfect results. Meanwhile, the definition of quality is linguistically, quality improvement consists of two words, namely improvement and quality. The word improvement means the process, method, or act of improving (business, activity, etc.). Meanwhile, the word quality means quality or (measurement of) the good and bad of an object, level, level/degree (smartness, intelligence, and so on). The concept of improving quality in education is managed through the school-based quality improvement management process (MPMBS) which is the embryo of school-based management (MBS). In MPMBS, the concept of improving school quality should be programmed, planned and carried out independently by the school based on the school's own needs to achieve success. Keywords: PAI Curriculum Development, Improving the Quality of Learning